Children's Behavioral Problems and the Need for Digital Guidance Services: A Survey of Kindergarten Teachers in Indonesia - Listiana, Aan; Hikmatyar, Aditya Aditama Putri; Bacotang, Juppri; Rachmawati, Yeni; Mariyana, Rita (Universitas Islam Negeri Raden Intan Lampung, 2026)
Behavioral problems in early childhood represent a persistent challenge for kindergarten teachers, particularly in low- and middle-income country contexts where access to professional counseling and child mental health support is severely constrained. This study aimed to (1) identify the types and frequency of children's behavioral problems most commonly encountered by kindergarten teachers in Indonesia, and (2) examine teachers' perceived needs for the features of a digital guidance service application. Employing a descriptive quantitative needs assessment design, data were collected from 115 kindergarten teachers across diverse regions of Indonesia (West Java, East Kalimantan, Maluku, and South Sumatra) via an online questionnaire. The instrument, comprising 15 Likert-scaled application feature items, demonstrated strong psychometric properties (Cronbach's α = 0.92; KMO = 0.87). Physical aggression (hitting/pushing peers) was the most prevalent behavioral problem (51.7%), with 69.8% of teachers encountering behavioral problems at least three times per month. All 15 digital application features received positive evaluations (means: 3.95–4.60). Practical handling tips (M = 4.60), video tutorials (M = 4.59), and informational articles (M = 4.58) were ranked highest. Professional consultation features were positively evaluated but ranked lower than self-accessible educational resources. These findings provide an empirical foundation for developing teacher-centered digital guidance services that are practical, affordable, and contextually responsive to the realities of early childhood education in Indonesia. Future experimental and participatory design studies are warranted to validate and translate these needs into effective application features.